Кровеносные сосуды червеобразного отростка кролика - Ильин, В.Е. (Вестник зоологии, 1976)
Angierentgenographic and macro-microscopic analyses were applied to study vermiform appendix lumen in rabbit. Passage and distribution of appendicular artery are described. In the appendix wall a great number of intervascular arterial in venous stomata is found. Lymphoid follicles of appendix possess a complex microcirculatory net. By the character of blood supply rabbit vermiform appendix is similar to human one.